Strategic Plan for international expansions of medical product ANESA - Kotliarenko, Taisiia; Kubíček, Aleš; Ali, Tanweer; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis focuses on developing recommendations for strategic international expansion for the unique patented medical device ANESA, produced in Ukraine. ANESA is a medical device for assessing an individual's health condition based on the analysis of the thermodynamic parameters of a body. The project includes two parts. The theoretical part reviews existing tools for foreign expansions, ways of market entry methods using external analysis (PESTEL), competitive analysis (Porter’s Five Forces Framework), and internal analysis (VRIO, SWOT). In the practical part, the strategy for entering the foreign market is formulated on the basis of the previously outlined analyses, with an emphasis on ANESA’s competitive advantage in the market. Furthermore, this part aims to showcase the significance of the company’s innovations to the global market. The conclusion forms strategic recommendations based on two previous parts, emphasizing the importance of aligning the company’s core values and mission with the demands of the foreign market.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses